2019
DOI: 10.1186/s12991-019-0233-7
|View full text |Cite
|
Sign up to set email alerts
|

Burden among caregivers of people with mental illness at Jimma University Medical Center, Southwest Ethiopia: a cross-sectional study

Abstract: Background Burden of caregivers of people with mental illness (PWMI) is considered to be a negative impact of the care provided by the family to the patient. However, little is known about the extent of the burden among caregivers of PWMI in Ethiopia. The aim of this study, therefore, is to assess the magnitude and associated factors of burden among caregivers of PWMI at Jimma University Medical Center, 2017. Methods Institution-based cross-sectional study design was em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
50
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 37 publications
3
50
1
Order By: Relevance
“…As pointed out in previous studies (Ayalew et al 2019; Demarco et al 2015), lower income was associated with the manifestation of burden. Among men, when compared to individuals who had a family per capita income of 1 minimum wage or more, those situated in the lowest income stratum (up to half a minimum wage) had a 3.24 higher chance of presenting with the outcome.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…As pointed out in previous studies (Ayalew et al 2019; Demarco et al 2015), lower income was associated with the manifestation of burden. Among men, when compared to individuals who had a family per capita income of 1 minimum wage or more, those situated in the lowest income stratum (up to half a minimum wage) had a 3.24 higher chance of presenting with the outcome.…”
Section: Discussionmentioning
confidence: 54%
“…Covariates related to family support and satisfaction with family relationships were associated with the outcome in both groups. It is noteworthy that these covariates were previously scored in the literature as markers of emotional and psychological illness among caregivers of people with mental disorders (Ayalew et al, 2019; Treichel et al, 2020). Overall, the results of this study corroborate the perspective that the functionality of the family can be affected by the care relationships, and this must be taken into consideration when proposing a care plan for the user and their family.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the less effective coping strategies noted by the caregivers in the current study were avoidance, ignoring, and engagement with the person’s non-reality-based thinking (i.e., hallucinations and delusions). These are also reflected in caregivers of people with mental disorders in other countries for example in Zimbabwe, Ethiopia, and India [ 7 , 35 , 36 ]. It should be noted that the majority of caregiving was provided by women, making them more susceptible to caregiver burdens [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…24 A cross-sectional study from south west Ethiopia reports substantially high level of caregiving burden; nearly, three-fourth of caregivers report moderate/severe objective burden and more than 97% of participants feel burdened subjectively 25 Jayakrishnaveni C et al in 2018 observed in his study that burden is comparable in all domains except schizophrenia patients 'caregiver experience more financial burden. 26 Another study from China shows that burden perceptions of clinical features like violent and suicidal behaviours were more in caregivers of acute bipolar patients than caregivers of schizophrenia patients. 27 Our study demonstrates that caregivers experience considerable amount of distress as a result of the care giving role, and are vulnerable to developing minor psychiatric disorders such as anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%